Are numbers special? An overview of chronometric, neuroimaging, developmental and comparative studies of magnitude representation. - Cohen Kadosh, R; Lammertyn, J; Izard, V (2008)
There is a current debate whether the human brain possesses a shared representation for various types of magnitude such as numerical quantities, physical size, or loudness. Here, we critically review evidence from chronometric, neuroimaging, developmental and comparative fields, and supplement it with a meta-analysis of the neuroimaging data. Together, based on such an integrative overview, we discuss limitations inherent in each approach, and the possibility whether shared, or distinct magnitude representation, or both representations exist.